Preliminary Investigation of Collecting Malaysia Web Pages Using Automated Traversing Tool - Abu Bakar, Zaitun; Sock Yin, Tai (Malaysian Journal of Computer Science, 2004)
Over the past few years, Malaysia web pages have gained popularity in the internet due to the increasingly strong demand of localized contents. Such huge document sets have introduced many new challenges to efficiently search among all other web pages. This study investigates the use of an automated traversing prototype that implements breadth-first and depth-first approaches to gather Malaysia web pages from the web. In the introduction, we describe the web structure and traversing approaches. Then, we discuss briefly on the experimental set-up that investigate the process of automating web traversal process to gather Malaysia web pages and compare the quality of information found using the two different traversing approaches i.e. breadth-first and depth-first. This is followed by a presentation of the results obtained and its analysis. Finally, the paper describes how the use of these traversal approaches can achieve different results.